Essay on the interaction between external debt and capital outflow from Russia - A. V. Ponomarev; V. A. Borisenkov (Vestnik MGIMO-Universiteta)
The article is devoted to interaction between capital outflow and external debt. We analyze the debt capital market in Russia in 2000s and provide a mechanics of crisis in 2008 – 2009. Based on the theory of R. Caballero and S. Panageas we offer a hypothesis concerning a reform in international reserves management. We believe Russian authorities should pay more attention to the regulation of capital outflow in a short period.